ANALISIS MANAJEMEN PEMBIAYAAN PENDIDIKAN MELALUI SYAHRIAH TERPADU DI PESANTREN DARUSSALAM BLOKAGUNG - Siti Aimah; Nur Khalimah (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
The aims of this study were to find out: 1) the implementation of education financing management through integrated sharia at the Darussalam Blokagung Islamic Boarding School, 2) the implications of education financing management data through integrated sharia at Darussalam Blokagung Islamic Boarding School. The type and research approach used is descriptive qualitative. The collection method used in this study is in-depth interviews, observation, documentation. Checking the validity of the data using triangulation. As for data analysis using interactive analysis of three models which include data reduction, data presentation, drawing conclusions. The results of the study show that: 1) implementation of education financing management through integrated sharia are: a) deliberations of foundation administrators and system managers, b) Education Financing System Design, c) determination of nominal payments, d) recruitment of the system management team, e) determination of team responsibilities managers, f) coaching for managers, g) preparing payment system applications, h) making Darussalam SIS applications, i) online and offline system socialization, j) periodic system evaluation meetings, k) payment recap reports. 2) implications for education financing management through integrated sharia are: a) form a team to handle payment arrears, b) increase banking cooperation, c) seek to increase the productivity of manager performance, d) seek solutions to disruptions to banking transaction trouble systems, e) provide socialization and assistance to some guardians of students who are technologically illiterate (clueless).